Engineered fluorescent carbon dots and G4-G6 PAMAM dendrimer nanohybrids for bioimaging and gene delivery - Martins, Ivo (2022)
ABSTRACT: Carbon dots (CDs) and G4-G6 (polyamidoamine)- PAMAM-NH2 dendrimers were self-assembled to produce CDs@ PAMAM nanohybrids for transfection and bioimaging purposes. CDs were synthesized by the hydrothermal method, using ascorbic acid as a starting precursor and characterized by transmission electron microscopy, UV−Vis, and fluorescence (in solution and solid-state) techniques. CDs were electrostatically combined with PAMAM dendrimers at room temperature, and the UV−Vis, fluorescence, and NMR spectroscopies were used to confirm the self-assembly. When compared to pristine CDs, nanohybrids were more photostable, resisting high acidic and basic pH. Moreover, they were considerably internalized by cells, as assessed by flow cytometry and fluorescence microscopy, and, when excited, displayed multi color emission easily quantified and visualized. These nanoscale hybrids, coined hybridplexes, can condense pDNA and transfecting cells successfully, particularly the G5 CDs@PAMAM nanohybrids. In summary, CDs prepared in mild and smooth lab conditions, showing good optical properties, were used to prepare elegantly CDs@PAMAM nanohybrids with promising biomedical applications.